PREMISES AND PERSPECTIVES FOR A GRAND STRATEGY IN OF THE 20TH AND 21TH CENTURIES - Baubinaitė, Kristina (Politologija, 2015)
Grand Strategy is a focused application of all available instruments of power and influence to assure survival and security of a nation, a State or that of their associations. The Article focuses on Grand Strategy demand and purpose problem in the 21st Century. Modern Grand Strategy – i.e. 20th and 21st Century – represents the object of this article. The United States, Germany, the United Kingdom and France all do possess different Grand Strategies, distinct methodologies of justification for the use of power and, also, various strategic cultures. E.g., the United States never had powerful neighbors nor had it faced the necessity to accommodate itself to the practices of other States, therefore American culture of the Grand Strategy is characterized by the “can do strategic culture” concept. Notwithstanding, West European strategic culture is a culture of compromises. As nation states have lost their exceptional privilege to be sole architects of international relations and whereas “substantially serious” threats that aim on a regular basis to sharply focus the human thought are absent, there can be recorded no sufficient ambition to contemplate on the terms of Grand Strategy. Presently, one is forced to speak not of Grand Strategies of particular States, but of the phenomenon of Grand Strategy of the Western world, that is build upon postulates of the liberal democracy development. Liberal democracy as a global and unique foundation to the Grand Strategy, its core leitmotif and, eventually, as its sole theoretical substantiation has gone mainstream in the Western world political discourse and academia, raises legitimate inquiries on the need of separate national Grand Strategies, their content, construction purposes and feasibility. The so-called social networking (network society) theory suggests one of the possible responses. Our world today is shaped by incomparable vectors of globalization and dissemination of various identities. IT revolution and restructuring capitalism have both helped in formation of a new type of society – the network society. Consequences of the network society formation to the nation states’ abilities to strategically plan their future are fundamental. State is only capable to project its development connecting such projections to the global context and accommodating its interior policies to the global competition requirements. In this context, it is vital to reconstruct definitions contributing to our efforts to comprehend power links that describe modern society, so that these definitions would not be based upon necessary link between a nation and a state as prerequisites and would clearly separate identity from instrumentality. One must discern new power relations that are by no means controlled by a nation state. Power relations represent ability to employ global instrumental networks via concrete forms of identity, whilst aiming to achieve transnational instrumental objectives. In this case, core ambition of the Grand Strategy of the nation states would be to reveal how power relations, not limited by State, are capable to remain a main component in State practice. In the course of two decades, one can observe a national Grand Strategy renaissance in the United States as the study object. American historian John Lewis Gaddis points to the process of “desecuritization” that commenced in the aftermath of the Cold War, with the Western citizens experiencing a phenomenon of mind “data erase”when it comes to the possibility of immediate threats, which by no means signifies the world development would continue only on positive path. We ourselves bear the responsibility for security and development of the postmodern society and for that cause a cohesion and scientifically substantiated qualities that enable us to analize and generalize contemporary phenomena (contemporary threats included) become assets of an extreme importance. Development success for the Western Grand Strategies model, one based upon the concept of liberal democracy, would depend not only on globalization or logic of the speedily developing network societies, but also on the properly calculated and conclusive political decisions of the national governments. If the Western States are feeling secure only when global democratic liberal order is in action, it will not take long for them to realize this sort of security comes at a price of grand efforts. Now this is exactly the time you might wish to turn to the Grand Strategies.